АНТИ-ҐЕНОЦИДНА КОНВЕНЦІЯ ООН І УКРАЇНСЬКИЙ ГОЛОДОМОР* (Zaporizhzhia Historical Review, 2021)
The article analyzes the 1948 United Nations Convention on Genocide and examines its applicability to the Ukrainian famine of 1932-1933. It was previously known that the mass starvation of Ukrainians resulted from exorbitant grain procurements, and subsequent punitive confiscations of other foodstuffs. Recently declassified Soviet documents make it clear that this destruction of human life was intended. The Communist Party's policy of "indigenization" of Soviet rule in the Ukrainian milieu took the form of cultural "Ukrainianization". Ukrainianization stimulated national revival in the Ukrainian SSR and among the 8,000,000 Ukrainians living in the Russian SFSR, especially the predominantly Ukrainian Kuban region. Stalin decided to break the backbone of the Ukrainian nation by starving to death a significan portion of the Ukrainian farmers and decimating the Ukrainian cultural, social and political elites. Ukrainianization was replaced by slow Russification in the URSS and completely abolished in the RSFSR.